Assessing potential environmental impacts of pesticide usage in paddy ecosystems: A case study in the Deduru Oya River Basin, Sri Lanka - Jayasiri, Maveekumbure M. J. G. C. N.; Yadav, Sudhir; Propper, Catherine R.; Kumar, Virender; Dayawansa, Nandani D. K.; Singleton, Grant R. (Oxford University Press, 2022)
Rice paddies are unique ecosystems that provide rich wetland habitat. Their enduring existence across vast stretches of land has led them to evolve into unique systems serving a diverse assemblage of organisms and sustaining a staple grain for many people. With food demand rising, agricultural intensification through agrochemical application is a common practice used to boost food production in developing countries, including Sri Lanka. The aim of the present study was to assess the concentration of pesticide residues in water in rice ecosystems and discover their potential impacts on both environmental health and the most common fauna groups across a cropping year in Sri Lanka. A total of 270 water samples from waters associated with paddy fields within a watershed were analyzed for 20 commonly used pesticides; in addition, local farm holders were surveyed to assess pesticide usage details in three selected paddy tracts. We then used the Cornell University environmental impact quotient (EIQ) calculator and the ECOTOX Knowledgebase to determine the exposure risk associated with individual pesticides relative to their application rates and aquatic concentrations. Survey results demonstrate that several pesticides were overapplied at rates 1.2–11 times the recommended application, and the EIQ demonstrated high environmental risk of two of the agrochemicals detected, 2‐methyl‐4‐chlorophenoxyacetic and diazinon. Fish, amphibians, insects, and beetles were found to have a wide range of potential adverse outcomes from exposure to diazinon, captan, thiamethoxam, and chlorantraniliprole. To balance the trade‐offs between food security and ecosystem sustainability, the present study recommends that adoption of quantifiable environmental health indicators be considered as part of the national policy regulating pesticide use. Environ Toxicol Chem 2022;41:343–355. © 2021 The Authors. Environmental Toxicology and Chemistry published by Wiley Periodicals LLC on behalf of SETAC.